2017
DOI: 10.1038/boneres.2016.49
|View full text |Cite
|
Sign up to set email alerts
|

Unintended targeting of Dmp1-Cre reveals a critical role for Bmpr1a signaling in the gastrointestinal mesenchyme of adult mice

Abstract: Cre/loxP technology has been widely used to study cell type-specific functions of genes. Proper interpretation of such data critically depends on a clear understanding of the tissue specificity of Cre expression. The Dmp1-Cre mouse, expressing Cre from a 14-kb DNA fragment of the mouse Dmp1 gene, has become a common tool for studying gene function in osteocytes, but the presumed cell specificity is yet to be fully established. By using the Ai9 reporter line that expresses a red fluorescent protein upon Cre rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 26 publications
4
63
0
Order By: Relevance
“…However, hormone deficiency during the rapid growing period induced a similar rate of trabecular bone loss in the Prx1; PRcKO mice in both sexes, suggesting that the ligand‐dependent role of PR signaling in the MSCs is directed at skeleton accrual. Additionally, Dmp1‐Cre targeted a broader cell population than osteocytes, and it is activated in early osteoblast lineage cells, in bone marrow cells and in tissue not related to bone . Selective deletion of PR in Dmp1+ cells resulted in a modest higher trabecular bone mass and bone strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hormone deficiency during the rapid growing period induced a similar rate of trabecular bone loss in the Prx1; PRcKO mice in both sexes, suggesting that the ligand‐dependent role of PR signaling in the MSCs is directed at skeleton accrual. Additionally, Dmp1‐Cre targeted a broader cell population than osteocytes, and it is activated in early osteoblast lineage cells, in bone marrow cells and in tissue not related to bone . Selective deletion of PR in Dmp1+ cells resulted in a modest higher trabecular bone mass and bone strength.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm other reports that Dmp1 marked a broader cell population than just the "osteocytes." (25,36,37) Distal femur trabecular BV/TV and middle femur cortical bone volume differed between the sexes in both the WT and mutant mice but were not different between the genotypes at 2 and 4 months of age (Fig. 6B).…”
Section: Pr Conditional Knockout In Osteocytes Marked By Dmp1 Resulmentioning
confidence: 94%
“…The 8kb Dmp1-Cre model showed a similar expression pattern, but with slightly less expression in osteoblasts. Lim and colleagues, using the same TdTomato reporter line [26], showed similar off target Dmp1-Cre expression and reported expression in a subset of gastric and intestinal mesenchymal cells. They further showed that deletion of the type IA BMP receptor using Dmp1-Cre resulted in the formation of polyps in the gastrointestinal tract, showing that Dmp1-Cre-mediated recombination caused an off-target phenotype.…”
Section: Cre Transgenic Mice Used For Studies In Osteocytesmentioning
confidence: 92%
“…In their original paper describing the 10kb-Dmp1-Cre mouse, using a ROSA26R-LacZ reporter model, Lu and colleagues reported Cre expression in osteocytes and odontoblasts postnatally, but saw little or no Cre expression during embryonic development and did not report notable off-target expression in other tissues [14]. However, recent studies using more sensitive TdTomato reporter lines crossed with Dmp1-Cre models have shown that Cre-mediated recombination may also occur in other cell types, leading to concerns about off-target effects [25, 26]. Kalajzic and colleagues used a reporter line, termed Ai9, that carries the Rosa-CAG-LSL-tdTomato-WPRE conditional allele (Jackson labs, #007905) in which Cre-mediated recombination causes activation of TdTomato expression.…”
Section: Cre Transgenic Mice Used For Studies In Osteocytesmentioning
confidence: 99%
“…Ultimately, a side‐by‐side comparison of how the two different Cre deleter strains “perform” with the same floxed gene of interest will be necessary to provide definitive proof for which strain is optimal for osteocyte‐“specific” gene deletion. Importantly, two recent studies using the 9.6 kB DMP1‐Cre strain in conjunction with a sensitive fluorescent reporter element demonstrate clear Cre‐dependent activity in non‐osteocyte cell types in and outside of bone . To date, the same systematic analysis of 8 kB DMP1‐Cre mice using sensitive fluorescent reporter elements has not been reported.…”
Section: Osteocytes As Pth Targetsmentioning
confidence: 99%